2022
DOI: 10.1155/2022/4149468
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Psoas Muscle Index with Fragility Vertebral Fracture: A Retrospective Cross-Sectional Study of Middle-Aged and Elderly Women

Abstract: Objective. To investigate the correlation of psoas muscle index (PMI) with fragility vertebral fracture. Methods. A total of 184 middle-aged and elderly women were included in the study. We measured the bilateral psoas muscle area on the picture archiving and communication system (PACS) from computed tomography images and calculated PMI. We observed lateral radiographs of the thoracolumbar spine and assessed vertebral fractures using the Genant semiquantitative method. The T-score, bone mineral density (BMD) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Zhang et al ( 47 ), in their postmenopausal women-based study, showed that a decrease in height, weight, BMI, bilateral psoas area and muscle index were associated with OP. They also observed that psoas muscle index of non-osteoporotic patients with vertebral fractures was lower compared to non-osteoporotic patients with non-vertebral fractures; they did not find a significant difference regarding psoas muscle index in osteoporotic patients with or without vertebral fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al ( 47 ), in their postmenopausal women-based study, showed that a decrease in height, weight, BMI, bilateral psoas area and muscle index were associated with OP. They also observed that psoas muscle index of non-osteoporotic patients with vertebral fractures was lower compared to non-osteoporotic patients with non-vertebral fractures; they did not find a significant difference regarding psoas muscle index in osteoporotic patients with or without vertebral fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they proposed that sarcopenia may be an independent risk factor for OVCF. 21 Additionally, Kajiki et al collected the clinical data of 87 patients and analyzed the relationships between psoas muscle index, bone mineral density, and fracture risk. They found that the psoas muscle index was significantly correlated with BMD and fracture (r = 0.413 and r = −0.545, both P < 0.001).…”
Section: Discussionmentioning
confidence: 99%